Dictyota cyanoloma (Dictyotales, Phaeophyceae), a Newly Introduced Brown Algal Species in California. Issue 1 (22nd December 2020) - Tran, Lan‐Anh T.; Bafort, Quinten; Steen, Frederique; Gómez Garreta, Amelia; D'Hondt, Sofie; Miller, Kathy Ann; Vranken, Sofie; Žuljević, Ante; Smith, Jennifer E.; De Clerck, Olivier
Abstract : Here, we report for the first time the presence of Dictyota cyanoloma in southern California. Dictyota cyanoloma is conspicuous in harbors and bays by its distinctive bright blue‐iridescent margins. This species was originally described from Europe, but subsequent studies have revealed that it represented an introduction from Australia. The current distribution of D. cyanoloma comprises southern Australia and the North East Atlantic, including the Mediterranean Sea and the Macaronesian islands. The presence of D. cyanoloma in southern California is supported by molecular cox 1 and psb A gene sequences. A reconstruction of the invasive history based on nine polymorphic microsatellite markers reveals a close affinity of the Californian specimens with European populations. Dictyota cyanoloma in the United States appears to be (so far) restricted to the Californian coast from San Diego Bay in the south to Santa Catalina Island and Long Beach Harbor in the north. A correlative species distribution model suggests gradually declining habitat suitability north of the Southern Californian Bight and high suitability in Baja California, including the Gulf of California. Finally, its widespread abundance in bays and harbors suggests shipping is a likely transport mechanism.